Analysis of medical expenditure and socio-economic status in patients with ocular chemical burns in East China: a retrospective study - Le Qihua; Chen Yan; Wang Xin; Hong Jiaxu; Sun Xinghuai; Xu Jianjiang (BMC, 2012)
Abstract Background Little has been known regarding the relationship between ocular chemical injury and victims' medical expenditure, income loss and socio-economic status changes. So we conduct this retrospective cross-sectional study in patients with ocular chemical burns in East China. Methods Fifty-six patients were enrolled and required to complete a self-report questionnaire consisting of the following contents: entire expenditure on medical treatment; the victims' personal and household per capita income, and income loss caused by the injury; and the changes of socioeconomic status as well. Results The median expense of medical treatment was CNY 40,000 (approximately US$5,900). The medical expenditure rose significantly with increased injury severity, prolonged hospital stay, and increased frequency of surgery. More than half victims (51.8 %, 29/56) paid all or the majority of medical expense by themselves. The expense of only 5 victims was mainly paid by medical insurance, accounting for less than ten percent (8.9 %, 5/56). The victims' personal and household per capita income both decreased significantly after the injury, with the median reduction being CNY 24,000 and CNY 7,800 (approximately US$3600 and US$1200) per year respectively. The reduction amplitude of personal and household per capita income rose with increased injury severity and prolonged time of care required. The injury caused emotional depression or anxiety in 76.8 % (43/56) victims, and the relationship with their relatives got worse in 51.9 % (29/56) patients. Moreover, only 21.4 % (12/56) patients felt that the whole society gave them care and concern after the injury, whereas 46.4 % (26/56) and 28.6 % (16/56) felt indifference or discrimination from society as a whole (X2 = 16.916, P = 0.028). Conclusions The medical expense was a huge economic burden to most victims of ocular chemical burns, and personal and household per capita income of the victims decreased significantly after injury, both of which had a close relationship with the injury severity. Formal legislation was urgently needed to compel the employer to purchase injury or medical insurance and provide more compulsory protection to the population working in high risk occupations. In addition, psychological counseling and instruction shouldn't be neglected in the aid and treatment of victims.